Optimalisasi Top Down Network Design terhadap Peningkatan Pemberdayaan Pelayanan dalam Menggunaan Mikrotik - Krisna Dexa (SAFE-Network, 2022)
The background of this research is about computer network services to students of the Faculty of Social and Political Sciences (FISIP) at Musi Rawas University, Lubuklinggau. The computer network used in FISIP is very slow, and sometimes it doesn't work well. The purpose of this study is to apply the empowerment of network services using Top Down Network Design in optimizing the use of Mikrotik routers for network connection services. The data processed in this study by conducting a field survey at FISIP Lubuklinggau City. The stages of the process start from observing the mechanism and analyzing QoS (Quality of Service). The method applied to optimize the network to improve service empowerment in the use of the Mikrotik network is Top Down Network Design. This method focuses on the application layer, so that it can be estimated the characteristics of the network to be designed and those that already exist before determining the device to be used. This research stage uses network development using the Top Down Network Design method, which consists of problem analysis, logical network design, physical network design, testing, optimization, and network design documentation. The results of data collection and calculation resulted in very good network conditions. There is one condition where when face-to-face lectures are still being conducted, the network conditions are not very good because of the density of data lines.